2015
DOI: 10.1001/jamapsychiatry.2015.0469
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and Environmental Influences on the Developmental Course of Attention-Deficit/Hyperactivity Disorder Symptoms From Childhood to Adolescence

Abstract: Importance Attention-deficit/hyperactivity disorder (ADHD) is conceptualized as a neurodevelopmental disorder that is strongly heritable. However, to our knowledge, no study to date has examined the genetic and environmental influences explaining interindividual differences in the developmental course of ADHD symptoms from childhood to adolescence (ie, systematic decreases or increases with age). The reason ADHD symptoms persist in some children but decline in others is an important concern, with implications … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
116
3
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 130 publications
(137 citation statements)
references
References 45 publications
17
116
3
1
Order By: Relevance
“…The investigators also reported a more stable pattern of inattentive symptoms compared to hyperactive symptoms, a finding that was reported in previous studies [56]. In a different study, 8395 twin pairs were assessed for ADHD at ages 8, 12, 14, and 16 with a DSM-IV ADHD symptom subscale [57]. Consistent with population-based and clinical studies, there was a general decline of symptoms across ages, and inattentive symptoms persisted more than hyperactive/impulsive symptoms.…”
Section: Evaluation and Prediction Of Trajectories Of Adhd Symptomsmentioning
confidence: 52%
“…The investigators also reported a more stable pattern of inattentive symptoms compared to hyperactive symptoms, a finding that was reported in previous studies [56]. In a different study, 8395 twin pairs were assessed for ADHD at ages 8, 12, 14, and 16 with a DSM-IV ADHD symptom subscale [57]. Consistent with population-based and clinical studies, there was a general decline of symptoms across ages, and inattentive symptoms persisted more than hyperactive/impulsive symptoms.…”
Section: Evaluation and Prediction Of Trajectories Of Adhd Symptomsmentioning
confidence: 52%
“…ADHD is a highly heritable disorder, with data from twin studies indicating that approximately 70% to 80% of the phenotypic variability is due to genetic influences (Faraone et al, 2005; Franke et al, 2012; Todd et al, 2001) and that heritability of clinically diagnosed ADHD remains high across the life span (Larsson, Chang, D’Onofrio, & Lichtenstein, 2014). Moreover, the developmental course of ADHD appears to have a strong genetic underpinning, with evidence for a primary role of genetic factors in ADHD symptom trajectories from childhood into adolescence (Pingault et al, 2015) and a higher familial risk for persistent ADHD than for ADHD that remits by adulthood (Franke et al, 2012). …”
Section: Discussionmentioning
confidence: 99%
“…Several longitudinal twin studies on ADHD symptoms report that new, age-specific genetic effects influence ADHD symptoms in adolescence and adulthood, suggesting that ADHD symptoms are a developmentally complex phenotype characterized by both continuity and change across the life span [3,9,12,13,19]. In addition, only a modest overlap between longitudinal genetic effects underlying both symptom domains (inattention versus hyperactivity/impulsivity) appears present, suggesting it is necessary to study both separately.…”
Section: Heritability Of Adhd Across the Lifespanmentioning
confidence: 99%